THE ROLE OF RELIGION LEADERS IN THE DISSEMINATION OF RELIGION, THE CONSTRUCTION OF MOSQUES. ABOUT THE MORAL LIFE OF DOSZHAN ISHAN KASHAK ULY(1815-1890) - Beknazarov Rakhym Agibaevich,; Rakhbayev Konysbay Kydyrbaevich, (Academic Journal of Physical and Chemical Sciences, 2020)
Doszhan Ishan Kashakuly (1815-1890) raised the spread of Islam in Western Kazakhstan to a new, higher level. The organization of a pilgrimage among the Kazakhs of the region, the construction of the Takiya house in the Arab country, in Mecca (Medina), the compilation of the Kazakh Genealogy and the 19th century. He is one of the most influential figures in the history of the Kazakh people, who worked tirelessly, demanding from the colonial government in the 80s "a separate mufti for the Kazakhs."